In Six Words…: Members of the Future Educators Association and Pi Lambda Theta Facebook communities describe their best day in the classroom. Issue 3 (February 2015) - Unknown
Members of the Future Educators Association and Pi Lambda Theta Facebook communities responded to the question, "How would you describe your best day in the classroom?" in six words.